2018
DOI: 10.1002/biof.1458
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of lycopene against chemical and natural toxins: A review

Abstract: People are exposed to a number of environmental, occupational, and therapeutic toxic agents which may be natural or man made. These hazardous substances may manifest as direct side effects on the function of organs or indirectly induced alteration of gene expression, cancer‐associated metabolic pathways, and/or alter homeostasis. Lycopene, as a one of the most potent antioxidant, is found in fruits and vegetables. High‐intake of lycopene has been shown to be effective in decreasing the risk of both natural tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 113 publications
0
62
0
1
Order By: Relevance
“…25 It has been commonly used as an antioxidant agent in traditional medicine and has been reported to have protective effects for the treatment of cardiovascular diseases, neurotoxicity, hepatic injury, and nephrotoxicity. 26 Acetaminophen overdoses are causes of hepatic necrosis and acute liver failure. 27 It has been reported that lycopene defends against acetaminophen-induced liver injury in mice by increasing antioxidant substances including GSH.…”
Section: Discussionmentioning
confidence: 99%
“…25 It has been commonly used as an antioxidant agent in traditional medicine and has been reported to have protective effects for the treatment of cardiovascular diseases, neurotoxicity, hepatic injury, and nephrotoxicity. 26 Acetaminophen overdoses are causes of hepatic necrosis and acute liver failure. 27 It has been reported that lycopene defends against acetaminophen-induced liver injury in mice by increasing antioxidant substances including GSH.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) ; Wu et al. (2017a) ; Hedayati et al. (2018) Cyanidin In vitro HepG2 & Caco-2 cells Protected against AFB 1 & OTA-induced oxidative stress Sorrenti et al.…”
Section: Mitigation Of Toxigenic Fungi and Mycotoxins Using Botanicalmentioning
confidence: 99%
“…Lycopene also prevented T-2 toxin-induced oxidative stress and maintained GSH cellular levels in vivo ( Leal et al., 1999 ). Furthermore, lycopene reduced AFB 1 and OTA-induced oxidative stress and apoptosis in rats ( Hedayati et al., 2018 ). Cyanidin, a phytochemical found in various medicinal herbs, fruits and vegetables including grapes, blackberry, cherry, cranberry, raspberry, red cabbage, red onion, etc., showed a protective effect against AFB 1 and OTA-induced toxicity in hepatocytes and enterocytes ( Sorrenti et al., 2012 ).…”
Section: Mitigation Of Toxigenic Fungi and Mycotoxins Using Botanicalmentioning
confidence: 99%
“…Paeonia lactiflora (Ma et al, ), Panax ginseng (Bak et al, ), and Coffea arabica (Cavin et al, ) are examples of such herbs. Apigenin (a flavonoid in some Apiaceae herbs; Sang et al, ), galangin (found in some Zingiberaceae rhizomes; Huang et al, ), glycybridin A & G ( Glycyrrhiza glabra ; K. Li et al, ), lycopene (Hedayati et al, ), and cyanidin (an anthocyanin found in different berry fruits; De Pascual‐Teresa, ) are a few examples of natural substances that have been reported to interact with Nrf2, potentially presenting health promoting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Paeonia lactiflora , Panax ginseng (Bak et al, 2016), and Coffea arabica (Cavin et al, 2008) are examples of such herbs. Apigenin (a flavonoid in some Apiaceae herbs; Sang et al, 2017), galangin (found in some Zingiberaceae rhizomes; Huang et al, 2017), glycybridin A & G (Glycyrrhiza glabra; K. , lycopene (Hedayati et al, 2019), and cyanidin (an anthocyanin found in different berry fruits;…”
Section: Introductionmentioning
confidence: 99%